The relationship between approach behavior and servicescape of event organized by Tourism Malaysia / Nor Azreen Kamaruddin - Kamaruddin, Nor Azreen (Faculty of Business and Management, 2006)
This research was conducted for the purposed of "The Relationship between Approach Behavior and Servicescape of Event organized by Tourism Malaysia". The main objective of this research was to determine the levels of customer satisfaction for the elements of servicescape that is physical facility, ambient condition, location and interpersonal condition whether to participate and lengthen the stay in the next event for the approach behaviour. The respondent of this study was hoteliers in Kuala Lumpur and Selangor. 80 questionnaires had been distributed to those hoteliers who participate the event organized by Tourism Malaysia. The researcher had used probability sampling and simple random sampling as the sampling technique. The conclusion of this study was the outcome from the survey analysis and findings. Through the research, it shows that majority of hoteliers who involved in the event organized by Tourism Malaysia found that the services were effective since objective of this study have been met.